Comparison of support strategies for grid construction after failure of renewable energy power generation system - Li, Ke; Lin, Xia; Zhu, Simeng; Wang, Long; Li, Qiang; Wang, Kun; Song, Shuxin (Frontiers in Energy Research, 2024)
As the proportion of renewable energy generation continues to rise, the study of voltage source converter (VSC) control has become a focal point of research. The concepts of emulating the characteristics of synchronous machines have led to the proposals of droop control and virtual synchronous control (VSG). However, a deeper comparison of the control characteristics of these two methods is still needed, particularly in terms of their ability to support the system when partial power sources experience fault conditions. This paper analyzes and compares the two in terms of control principles and small-signal modeling, and finally, based on a nine-bus system with 100% renewable energy generation, two scenarios are designed: a sudden load increase and a partial power source disconnection. The differences in control characteristics between the two are compared and analyzed. The results indicate that the VSG exhibits greater damping compared to droop control and is capable of providing inertial support to the system, making its frequency and voltage less susceptible to change.